1984
DOI: 10.1128/aem.47.5.1005-1011.1984
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods to measure acute metal and organometal toxicity to natural aquatic microbial communities

Abstract: Microbial communities in water from Baltimore Harbor and from the mainstem of Chesapeake Bay were examined for sensitivity to mercuric chloride, monomethyl mercury, stannic chloride, and tributyltin chloride. Acute toxicity was determined by measuring the effects of [3H]thymidine incorporation, [14C]glutamate incorporation and respiration, and viability as compared with those of controls. Minimum inhibitory concentrations were low for all metals (monomethyl mercury, <0.05 ,ug liter-1; mercuric chloride, <1 ,ug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(38 citation statements)
references
References 23 publications
3
35
0
Order By: Relevance
“…This notion is also needed for the Rhine Action Plan and the North Sea Action Plan, for which several metals, among them copper, are priority compounds. A previous study indicated that bacterial populations from the River Rhine responded very strongly to small additions of copper (Tubbing and Admiraal, 1991a), which tallies with observations in other waters (Vives Rego et al, 1986;Jonas et al, 1984). Although natural microbial populations may provide sensitive criteria for assessing effects on ecosystems, there are also a number of obstacles.…”
Section: Introductionsupporting
confidence: 65%
“…This notion is also needed for the Rhine Action Plan and the North Sea Action Plan, for which several metals, among them copper, are priority compounds. A previous study indicated that bacterial populations from the River Rhine responded very strongly to small additions of copper (Tubbing and Admiraal, 1991a), which tallies with observations in other waters (Vives Rego et al, 1986;Jonas et al, 1984). Although natural microbial populations may provide sensitive criteria for assessing effects on ecosystems, there are also a number of obstacles.…”
Section: Introductionsupporting
confidence: 65%
“…['4C]Glucose turnover in pond water [20] and in river water [6] and amino acid turnover in estuarine waters [19] were as sensitive to the addition of 10 to 100 pg L-' copper as thymidine incorporation was in our study. Jonas et al [7] opined that thymidine incorporation should be a more universal parameter for testing acute toxicity of compounds than the activity specific to certain types of bacteria, e.g., sulfate reduction, because thymidine is so upiversally utilized by bacteria. Any interference of a toxicant with the cellular metabolism of heterotrophic bacteria would thus be detected.…”
Section: Relative Sensitivity Of Microbial Parametersmentioning
confidence: 99%
“…Numerous studies have indicated that metabolic processes of microorganisms are very sensitive to pollutants [2,3] and hence the in situ activity of microbial communities has been used for establishing the effects of perturbations. The responses of aquatic bacteria to toxicants have been studied with various microbial techniques, including respiratory activity [4], acetate incorporation, glucosidase activity [ 5 ] , and, more recently, glucose metabolism [6], thymidine incorporation [7,8], and enzyme activity [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…These observations reinforce the conclusion that the chemical species of a metal is important. Jonas, et al (1984) used four methods to estimate minimum inhibitory concentrations (MIC) for natural bacterial populations from Chesapeake Bay exposed to mercury and tin compounds (Table VII). MIC values were at least ten times lower when measured using radiolabeled substrates as when measured by plate counts.…”
Section: How You Assay Influences the Apparent Toxicitymentioning
confidence: 99%